Architectural Plasticity: The Aesthetics of Neural Sampling. (7th April 2022) - Koh, Immanuel
Abstract: Director of Artificial‐Architecture at the Singapore University of Technology and Design (SUTD), Hokkien Foundation Career Professorship recipient Immanuel Koh enlightens us on the wonderful world of deep neural networks, formal plasticity and what they could mean for architectural form‐finding.